A diversificação nas formas de oferta do ensino médio no Estado do Pará: análise das Regiões de Integração do Marajó e Metropolitana - COELHO, Sandy Caroline Seabra (2020)
This study aims to analyze the different forms of provision of secondary education in paraense, specifically in the Integration Regions of Marajó and Metropolitan, and the reproduction of socioeconomic inequalities. As a methodological procedure, the bibliographical and documentary review was chosen, as well as the collection and analysis of statistical data. The results show that there are approximately nine ways to offer high school in the state, this number may increase if we consider some variables such as shift and location. We consider that the different forms of access to secondary education, at the same time as they can reveal possibilities of diversification, may also present limits on increasing school inequalities, because in the context of society divided into social classes there is a tendency to promote hierarchization among the different schools, specifically in the public school system. The data collected are a partial picture of the context of the high schools of paraense and do not explain all the contradictions associated with this teaching, but they express current numbers, pointing to marked indices of educational inequalities produced by social inequalities.